VARIASI KETEBALAN MEDIA PADA BIOSAND FILTER TERHADAP PENURUNAN BAKTERI COLIFORM PADA AIR BERSIH DI PACKING HOUSE XYZ (Jurnal Kesehatan Siliwangi, 2021)
The need for clean water used for sanitation and production facilities in the Packing House XYZ comes from drilled wells. The water quality contains Coliform Bacteria contaminants. Plans to deal with this problem can use several ways, one of which is a Biosand Filter. This study aims to determine the variation of media thickness on Biosand Filter to decrease Coliform Bacteria in clean water. This type of research is experimental with a posttest with control research design. Variations in thickness of the Biosand Filter media used were 80 cm (60:10:10), 95 cm (65:15:15) and 110 cm (70:20:20) whose composition was silica sand: coconut shell activated carbon: gravel. After the One Way Anova test, the P value was 0.928 (α > 0.05) so that there was no significant difference in the variation in the thickness of the filter media. The variation of media thickness in Biosand Filter which is the greatest in reducing Coliform Bacteria is at a media thickness of 110 cm reaching 95.33% so that the Biosand Filter is good at reducing Coliform Bacteria to below the quality standard. It is recommended for the industry to use a Biosand Filter with a media thickness of 80 cm as an alternative to reduce Coliform Bacteria and further research needs to be carried out using different sand and activated carbon media.